Fetal QT interval detection from abdominal ECG signals by using iterative independent component analysis / Fatima Azzahra Manap - Fatima Azzahra , Manap (2019)
Prenatal cardiac monitoring is an aspect of utmost importance in early detection of fetal distress. Currently, electronic fetal heart monitoring is used on the majority of pregnancy episodes in the developed world to identify risk situations for both mother and fetus. Fetal heart monitoring also provide valuable parameters such as fetal heart rate (FHR), fetal RR and fetal QT (FQT) interval. This study focuses on the systematic methods for accurately locating the fetal QRS complexes and estimating the QT interval in non-invasive fetal electrocardiogram (NIFECG) signal from a single lead abdominal recorded electrocardiogram (ECG). NIFECG signals are usually corrupted by many interfering sources. Most significantly, by the maternal ECG (MECG), whose amplitude usually exceeds that of the fetal ECG (FECG) by multiple times. The presence of additional noise sources further affects the signal-to-noise ratio (SNR) of the FECG. The methods included four steps. In step one, the autocorrelation function was used to detect and remove the maternal QRS (MQRS) complex from the abdominal FECG signals. Then, a filtering method used to pre-process and remove noise from the signals. After the pre-processing the obtained FECG signals, the fetal R-peaks (FR-peaks), fetal RR and FHR were determined by a stationary wavelet transform. Finally, an Iterative Blind Source Separation Method approach was implemented in order to determine the FQT intervals. It was shown, that the NIFECG can allow accurate estimation of the FQT interval, which opens the way for new clinical studies on the development of the fetus during the pregnancy. The single lead FHR detection is particularly useful. This dissertation addresses the current aspects of NIFECG analysis and provides future suggestions to establish NIFECG in clinical settings.